Pengaruh Bioaktivator MOL (Mikroorganisme Lokal) Jerami Nangka (Artocapus integra merr) terhadap Lama Pengomposan - Vransisko Busa, Mario; Maria Yasinta Moi; Yulimira Syafriati Yuminar Mutiara Sani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The purpose of the study was to determine the effect of the bioactivator MOL Jermai Jackfruit (Artocapus integra merr) on the length of time for composting. Jackfruit straw is one of the wastes that has not been used properly and is thrown away so that it can cause environmental pollution. So to avoid this problem, the Jackfruit Straw is fermented into MOL as a compost material from organic vegetable waste, fruits are thrown away and produce a bad smell. MOL Jackfruit Straw was fermented for 7 days with a brown color and smell of alcohol. The research method used experimentally by using 3 variables, namely the independent variable (long composting time), the dependent variable (MOL Straw Jackfruit) and the supporting variables EM4 and control. The results of the research composting using MOL Straw Jackfruit, EM4 and control temperature of the compost 300C, pH 7, 70% content, blackish color, smooth texture and smell like soil. The final composting process in all treatment parameters has met the SNI for compost except the water content, namely the temperature according to ground water (300C), pH 6.80-7.49, maximum water content of 50% blackish color, texture and smell like soil. The length of time for composting using MOL Straw Jackfruit dose of 10 ml 24 days, EM4 10 ml 29 days and control 42 days. Data analysis using the Kruskal-Wallis test obtained a significance value of 0.000 < 0.05, so H1 is accepted or there is an effect of the Jackfruit Straw MOL bioactivator on the length of time for composting.